Cardiac and Inflammatory Necrotizing Enterocolitis in Newborns Are Not the Same Entity - Klinke, Michaela; Wiskemann, Hanna; Bay, Benjamin; Schäfer, Hans-Jörg; Pagerols Raluy, Laia; Reinshagen, Konrad; Vincent, Deirdre; Boettcher, Michael (Frontiers in Pediatrics, 2021)
Background. Necrotizing enterocolitis (NEC) is an often-fatal neonatal disease involving intestinal hyperinflammation leading to necrosis. Despite ongoing research, (1) conflicting results and (2) comorbidities of NEC patients make early NEC detection challenging and may complicate therapy development. Most research suggests that NEC pathogenesis is multifactorial, involving a combination of (1) gut prematurity; (2) abnormal bacterial colonization; and (3) ischemia-reperfusion (I/R) injury. As neutrophil extracellular traps (NETs) partially mediate I/R injury and drive inflammation in NEC, we hypothesized that NETs contribute to NEC development; particularly in cardiac patients. Methods. A retrospective analysis of baseline characteristics, clinical signs, laboratory parameters, and imaging was conducted for surgically verified NEC cases over ten years. Patients were stratified into two groups: (1) prior medically or surgically treated cardiac disease (cardiac NEC) and (2) no cardiac comorbidities (inflammatory NEC). Additionally, histology was reassessed for neutrophil activation and NETs formation. Results. A total of 109 patients (cNEC 43/109 vs. iNEC 67/109) were included in the study, with cNEC neonates being significantly older than iNEC neonates (p=0.005). While no significant differences were found regarding clinical signs and imaging, laboratory parameters revealed that cNEC patients have significantly increased leucocyte (p=0.024) and neutrophil (p<0.001) counts. Both groups also differed in pH value (p=0.011). Regarding histology: a non-significant increase in staining of myeloperoxidase within the cNEC group could be found in comparison to iNEC samples. Neutrophil elastase (p=0.012) and citrullinated histone H3 stained (p=0.041) slides showed a significant markup for neonates diagnosed with cNEC in comparison to neonates with iNEC. Conclusion. The study shows that many standardized methods for diagnosing NEC are rather unspecific. However, differing leucocyte and neutrophil concentrations for iNEC and cNEC may enable earlier NEC diagnosis and timelier intervention. As we propose that iNEC is grounded in sepsis and neutropenia, while cNEC primarily involves I/R injuries, which involves neutrophilia and NETs formation, it is plausible that I/R injury due to interventions for cardiac comorbidities results in pronounced neutrophil activation followed by a hyperinflammation reaction and NEC. However, prospective studies are to validate these findings and to determine the accuracy of the potential diagnostic parameters.